Policy Persistence and Rent Extraction - Silke Friedrich (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2011)
The existing literature has shown that special interest groups can have both growthenhancing and retarding effects on an economy. In either case it is always assumed thatthe nature of the special interest groups remains constant over time. The hypothesis ofthis paper is that a dynamic relationship exists between politicians and lobbyists. A theoreticalframework in which established and new lobbies overlap is developed to modelthe incentives a government might have to behave in a manner consistent with thehypothesis. In this structure despite the fact that they support projects from which allproductive benefits have been extracted politicians are still rationally reelected.
Keywords: D72; 330; Lobby; special interest; efficiency; elections; Interessenpolitik; Hysteresis; Politische Entscheidung; Rent Seeking; Wiederwahl; Theorie